2011
DOI: 10.1007/s11214-011-9759-y
|View full text |Cite
|
Sign up to set email alerts
|

LCROSS (Lunar Crater Observation and Sensing Satellite) Observation Campaign: Strategies, Implementation, and Lessons Learned

Abstract: a permanently shadowed region of the lunar surface to create an ejecta plume. The resultant impact crater and plume were then observed by the LCROSS Shepherding Spacecraft as well as a cadre of telescopes on the Earth and in space to determine the nature of the materials contained within the permanently shadowed region. The Shepherding Spacecraft then became a second impactor which was also observed by multiple assets.The LCROSS Observation Campaign was a key component of the LCROSS mission. The goal of the Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…This obscuration thus required material to ballistically rise above a height of 1.8 km in order to have been seen from Earth, thereby setting a strong limit on visible mass. Despite this limitation, a significant ground-based observing campaign was executed from the western United States and Hawaii to further characterize the LCROSS debris plume both spectroscopically and through imaging 9 . Aside from an enhancement of sodium in the lunar exosphere after the impact 10 , no other positive ground-based detections of the LCROSS debris plume were reported.…”
mentioning
confidence: 99%
“…This obscuration thus required material to ballistically rise above a height of 1.8 km in order to have been seen from Earth, thereby setting a strong limit on visible mass. Despite this limitation, a significant ground-based observing campaign was executed from the western United States and Hawaii to further characterize the LCROSS debris plume both spectroscopically and through imaging 9 . Aside from an enhancement of sodium in the lunar exosphere after the impact 10 , no other positive ground-based detections of the LCROSS debris plume were reported.…”
mentioning
confidence: 99%
“…The plume never reached an altitude where it was illuminated by the Sun and also above the foreground ridge of the Cabeus crater, which would have enabled Earth‐based observers to detect it. According to model calculations, this corresponds to an altitude of approximately 2.5 km [ Heldmann et al , 2011].…”
Section: Discussionmentioning
confidence: 99%
“…The spectral coverage afforded by the combination of instruments used on these three telescopes spanned 0.47–1.9 μ m. The spectral response of each camera and filter used for this study is shown in Figure 1, and the respective image scale parameters are listed in Table 1. The data acquired with each telescope are further described below, and additional details concerning the ground‐based LCROSS observing campaign, including the participation of the three telescopes described herein, are discussed by Heldmann et al [2011].…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lunar Reconnaissance Orbiter (LRO) passed by the impact site between the times of the Centaur and SSC impacts [ Gladstone et al , 2010]. Ground based observatories watched the event [e.g., Killen et al , 2010; Hong et al , 2011; Miller et al , 2009; Heldmann et al , 2011]. Thus, data were taken from multiple perspectives to determine the composition and quantities of materials in the ejecta.…”
Section: Introductionmentioning
confidence: 99%